О медицине в Херсонесе Таврическом - Кадеев, В. И. (Давнина. Харківський історико-археологічний щорічник, 2016)
Summary Kadeyev V. I. On Medicine in Ancient Chersonessus The paper is devoted to history of medicine in antique Chersonesus. Using evidences of archaeological and epigraphical sources, author draw conclusion thath in Chersonesus existed native medical school, foundated in the IV – III c. B. C. by inhabitants from Eastern Meditteranean. Vaious surgical and medical instruments confirm fairly high ievel of medicine in Chersonesus. Among physicians were terapeutists, surgeons, otologists. In the town existed the centre of medicine arisen by the temple of Asclepios. First century A. D. – time of appearance medical officers of Roman army, vcxillationes which accommodated in Taurica.